Diversifying endpoints in biodegradation testing of microplastics - Eva-Maria Teggers; Jonas Hardebusch; Boris Meisterjahn; Markus Simon; Dieter Hennecke; Roman Heumann; Holger Egger; Philipp Dalkmann; Andreas Schäffer; Annika Jahnke (Environmental Sciences Europe)
Abstract To counteract microplastic (MP) pollution the European Commission adopted a restriction of intentionally adding synthetic polymer microparticles to products, such as detergents, rinse-off cosmetics, controlled-release fertilizers or pesticides. Exempted are particles consisting of polymers that, e.g., meet the (bio)degradability pass criteria of the available test methods. The main criterion for proving biodegradability is the particle’s mineralization rate, as set out, amongst others, in OECD testing guidelines 301B  referenced by the REACH regulation of the European Union. Since present test methods are designed and validated to test low-molecular, soluble compounds adaptations regarding MP biodegradability testing are of high interest. In this study, the biodegradability of a polyurea (PUA) microcapsule suspension was tested using a standard degradation test method (OECD test guideline (TG) 301B). Since the polymeric component comprised less than 1% of the suspension, besides the aromatic solvent inside the microcapsule (8.6%) and water (90.9%), 14C-labeling of the polymer was essential for specific detection throughout the experiments. Particle size determination of the tested PUA microcapsules indicated a bias in the test results due to the presence of a soluble 14C-compound, a byproduct of synthesis, identified using ultra-high performance liquid chromatography–high resolution mass spectrometry (UHPLC–HRMS) coupled with radioactivity detection. This study highlights the need for proper characterization and purification of the tested particles prior to biodegradation testing and suggests how to diversify future regulatory testing for a comprehensive assessment of the biodegradation of MPs. Graphical abstract